Pengembangan Modul elektronik berbasis Flipped Classroom pada materi sistem sirkulasi untuk meningkatkan motivasi belajar siswa - Samsi, Irnayanti Fadhillah; Djukri (Postgraduate, University of Mataram, 2024)
The using of teaching materials has an important role to increase student learning motivation. This research and development aims to produce the Flipped Classroom based E-module that is appropriate, practical, and effective to increase students learning motivation on eleventh grade at senior high school. The research used a research and development methodology (R & D) with ADDIE development model through the phase of Analysis, design, development, implementation and evaluation. The data resources are material scholar, biology teacher, and the eleventh grade student at senior high school. The research instrument used a questionnaire. The data analysis used likert scale then the result of the research indicated that the product is appropriate based on the material scholar’s assessment is 97,91%, (very appropriate), and the media scholar’ assessment is 91,25% (very appropriate) the product is practically used based on biology teacher is 100% (very practical) and the result of small scale test obtained 89,66% (very practical). An E-module is effective to increase students motivation learning based N-gain score result 0,49